Perempuan dalam Kebertahanan UMKM Ratu Jaya pada Masa Pandemi Covid-19 di Kota Depok - Apriliani, Widhi; Wiasti, Ni Made; Murniasih, Anak Agung Ayu (Department of Anthropology Udayana University, 2023)
This study discusses the strategy of Women's Resilience in Ratu Jaya's Micro, Small and Medium Enterprises (UMKM) during the Covid-19 pandemic in Depok City, West Java Province. The focus of this research is the strategy to maintain UMKM carried out by women's groups during the downturn of Covid-19 by using the theory of structural functionalism from Talcot Parson and the theory of Liberal Feminism a la Alison Jagar. The method used to answer this research is qualitative ethnography with interviews and observations. Where the results of this study are women are able to maintain UMKM through various digital marketing and marketing strategies, maximizing relationships between members, transparency in administration and adaptation to the pandemic.